Weighted Index of Cultural Heritage Disclosure in Indonesia - Rizky Windar Amelia; Djoko Suhardjanto; Agung Nur Probohudono; Setyaningtyas Honggowati (Green Publisher Indonesia, 2022)
This study compiles a cultural heritage index that can be used as a measure of the company's attention to cultural heritage which can be seen from the disclosure of financial statements. From the results of the literature review, the matrix creation carried out, and the forum group discussions held with stakeholders, 19 items of the Cultural Heritage disclosure index were obtained. the average importance of Cultural Heritage Disclosure to be disclosed according to stakeholders was very high as indicated by the mean of each item of 5.26% from the total maximum of 5.49% and a minimum of 5.02%. This implies that the mean of each item of Cultural Heritage Disclosure according to stakeholders is equally important. This is also corroborated by the overall mean of demand for Cultural Heritage disclosure according to stakeholders of 6.22 on a Likert 7 scale. Compliance with law items (item related to the company's level of compliance with regulations of cultural heritage) occupied the highest weighted index, while incidents and fines items were the lowest weighted index